The influence of governance on the implementation of Public-Private Partnerships in the United Kingdom and China: A systematic comparison. (June 2020) - Wang, Nannan; Gong, Zheng; Liu, Yunfei; Thomson, Craig
Abstract: Although Public-Private Partnerships (PPPs) have been widely implemented in a number of countries, their development and governance contexts are different. This research investigates PPPs through the lens of governmentality and develops a systematic and innovative analytical framework to evaluate and compare the PPP governance in China and the United Kingdom. Based on the findings, a conceptual model is proposed to illustrate the conducting of PPP governance, by the governments involved. The research contributes to the literature on the governance of PPP by providing a clear framework and an assessment tool. The result can benefit the policymakers in different countries, in assessing and improving the efficiency and effectiveness of their PPP governance in practice, hence helping the decision-making of government in identifying and targeting loopholes in their PPP market. Highlights: Investigating PPP governance through the lens of governmentality. A systematic and innovative analytical framework to evaluate and compare the PPP governance between China and the UK. A conceptual model is developed to illustrates the conduct of PPP governance. Contribute to the literature on the governance of PPP and improving the efficiency and effectiveness of PPP.